Evaluation of serum magnesium levels among type 2 diabetes individuals of a South Indian town - Govindaraj Suganthi; Vijayakumar Praveen; Vajiravelu Suganthi; Panneerselvam Periasamy; Bagavathiammal Periyasamy; Sasikala Gunasekaran (Wolters Kluwer Medknow Publications, 2023)
Background: Studies have reported that hypomagnesemia could play an essential role in the development of endothelial dysfunction and altered insulin function, particularly among type 2 diabetes mellitus (T2DM). To assess the incidence of hypomagnesemia among patients with T2DM and compare them with healthy individuals. Materials and Methods: One hundred types 2 diabetic patients admitted to the general medicine outpatient Department at Government Erode Medical College Hospital, Perundurai, were recruited. Biochemical parameters and serum magnesium were assessed at admission and compared with the 100 healthy controls without T2DM. Results: Cases and controls had mean ages of 50.39 ± 9.76 and 50.01 ± 10.15 years, respectively. The age range of 41-50 had the highest percentage of patients (42%). The gender distribution was the same for both cases and controls, with 70% of men and 30% of women. Between cases and controls, the mean fasting blood sugar levels were 102.42 ± 11.16 mg/dl and 91.93 ± 4.32 mg/dl, respectively. Conclusion: Hypomagnesemia is a common problem in adults with T2DM, and we did find a significant association between Mg levels and T2DM in Erode district, Tamil Nadu.